Winning Hearts and Minds in Afghanistan? Examining the Relationship between Aid and Security in Balkh Province - Fishstein, Paul (Tufts Archival Research Center, 2005)
Afghanistan has been a testing ground for a key aspect of counterinsurgency doctrine, namely that humanitarian and development projects can help to bring or maintain security in strategically important environments, and by "winning hearts and minds" undermine support for radical, insurgent, or terrorist groups. The assumption that aid projects improve security has lead to a sharp increase in overall development funding, an increased percentage of activities programmed based on strategic security considerations, and a shift of development activities to the military. Given what is at stake, it is essential that policy makers understand whether and how aid projects can actually contribute to security.